American Jesuit Prisoners of War, 1942–1945 - Badillo, SJ (Archīum Ateneo, 2014)
When the Japanese occupied the Philippines in the Second World War,they put enemy aliens, including American Jesuits, in prison camps inseveral places in the country. Published accounts provide only partial listsof American Jesuit internees. Here is provided complete lists of Jesuitinternees in the prison camps at the University of Santo Tomas and in LosBaños. Also provided is the list of Jesuits who were never captured. Themethod used to compile the complete lists is given.Keywords: Second World War • Americans in the Philippines • Jesuits